(untitled) (Asian-Australasian Journal of Food Safety and Security, 2017)
A feeding trial was conducted to investigate the effect of Probiotic (Biofast) on the growth performance and meat quality of broiler chicken. Ninety six 1-d-old mix sexed Cobb 500 broiler chicks were obtained from a local commercial hatchery. Chicks were randomly allocated in 2 experimental treatments for 5 wk. The experimental treatments received a 1) control, 2) control with probiotic Biofast 0.055% (bacillus subtilis-100%) in the diet. Both treatments had 48 broilers arranged in 4 replicates of 12 broilers each. Eight birds from 2 different groups (one/replication) were sacrificed on termination of the feeding trial of breast, thigh to investigate the meat quality. Feed intake in treatment T1 was significantly (P > 0.05) greater than control in 0 to 3 weeks of age. Though in starter phase treatments failed to induce any marked effects on body weight, weight gain and FCR but numerically increased in T1 than control. In finisher period (4-5 wks), there were no significant differences on body weight, weight gain, feed intake and FCR between the treatments. The organ weight like liver, heart, kidney, spleen, gizzard, abdominal fat and intestine weight also did not show any significant differences between the dietary treatments of control and Biofast. In addition, though the dressing % was not significantly different but numerically higher percentage was found by using Biofast. Similarly, no significant differences (p>0.05) were found in pH, cooking loss, meat color and TBA values between the treatments. In conclusion, supplementation of Biofast in diet has no significant effect on the growth performance of broiler chicks though it has got some positive effects on other parameters that indirectly revealed to enhance meat quality of broiler chicken as well as food safety issues. Asian Australas. J. Food Saf. Secur. 2017, 1 (1), 51-57